Faceted Growth of Morphologically Tuned of BiOCl. (2019) - Sarkar, Ratna; Das, Dimitra; Mitra, Anuradha; Sarkar, Subrata; Kumar Chattopadhyay, Kalyan
Abstract: Bismuth oxychloride (BiOCl) is a p-type indirect gap semiconductor with a band gap of ∼3.2-3.5 eV, possessing interesting crystal structure, optical and electrical properties. Lately, its photocatalytic potential in the removal or decomposition of organic effluents like dyes, phenol, etc. from water has been highly explored. However, the larger prospective applications of BiOCl as catalysts, solar cells, pigments, gas sensors, etc. have made it of immense importance. Easy and robust synthetic strategy is essential for the precise control of different synthetic parameters. A detailed understanding of the formation mechanism is, therefore, of contemporary relevance. In this work, we have devised a simple and efficient way to precisely control the growth of (001) planes in BiOCl through variation of synthesis method and synthesis temperature. The structure and morphology of the as prepared samples were characterized using XRD and FESEM analysis. The morphology changed from nanoflakes to nanosheets with increase in temperature and by varying the synthetic strategy. The binding between the Bi and CA in the presence of –OH bonds were monitored through FT-IR, and Raman Spectroscopy. Diffused reflectance spectra revealed that the indirect band-gap of Bismuth oxychloride varies from 3.4-3.2 eV with the variation in its morphology. A correlation between the morphology, band structure and mechanism of preferential growth of some crystalline facets over the other has been critically studied. Moreover the as prepared samples have been utilized to degrade toxic Rhodamine B dye under visible light irradiation. The sample having nanoflakes like morphology completely degraded the organic dye in only 14 mins. The sample showed superior photocatalytic activity as compared to most reported literatures.